Hydrotropic Solvents Used For Extraction Techniques Of Barleria Elegans L. Leaves - Pal Singh, Rakesh; Joshi, D. B.; Bhadauria, R. S. (International Journal of Scientific Research and Management (IJSRM), 2022)
Plant species belonging to the family Acanthaceae are globally known to possess various medicinal properties and have cultural and economic importance in both traditional medicine and horticulture. They are important to both animals and humans and are used as food or for ornamental purposes worldwide. Barleria is the third largest genus in the family Acanthaceae. A few of the highly important and reported species of Barleria include B. prionitis, B. cristata, B. grandiflora, and B. lupulina. The flowers, leaves, stems, roots, and seed extracts of plants belonging to this genus are rich in bioactive compounds and have exhibited significant medicinal potential for the treatment of various ailments and infections.Hydrotropic agents are stated as ionic organic salts which help to increase or decrease the solubility of solute in a given solvent via ‘salt in’ or ‘salt out’ effects, respectively. Salts which show ‘salt in’ of non-electrolytes are called “hydrotropic salts” and the phenomenon is known as “hydrotropism. There are about 45,000 plant species in India, with concentrated hotspots in the region of Eastern Himalayas.Entire plants of Barleriaelegans collected from Shrinathji Institute of pharmacy, Nathdwara and the plant was authenticated by Dr. R.L. Bhardwaj. The leaves of Barleriaelegans plant was characterized by its morphological features like colour, shape, size and surface characteristics has been studies. The plant materials (500gm) were initially defatted with petroleum ether and then extracted with blends RP-1 to RP-6 using a Soxhlet apparatus. The yield of the plant extracts measured about 20 g each after evaporating the solvent using water bath. As per result of TLC, we found that the hydrotropic blends solution aurecoferindly and cost effective method for the extraction purpose. All the phytoconstitutents which was earlier reported in previous literature by the use of organic solvents which were also present for the use of hydrotropic solvents.